MEANING FULL STUDI KEISLAMAN: KURIKULUM BERBASIS CINTA PADA MADRASAH IBTIDAIYAH - Rama Adji Prasetya, M; Fadli Arafah, Ahmad; Zainuri, Ahmad; Fatimah Zahra, Frika (PT PUSTAKA CENDEKIA GROUP, 2025)
This article discusses the concept of meaningful Islamic studies combined with a love-based curriculum in Madrasah Ibtidaiyah (MI). This approach emphasizes learning that not only conveys religious knowledge but also builds emotional closeness between teachers and students so that Islamic values can be understood more deeply. By creating a warm, child-friendly, and life-relevant learning atmosphere, a love-based curriculum is able to provide meaningful learning experiences for MI-aged children. This article aims to describe the concept, implementation, and relevance of a love-based curriculum in strengthening students’ religious character. Through this study, it is expected that a new understanding will emerge regarding the importance of humanistic learning approaches in basic Islamic education.